2013
DOI: 10.1177/1087054713482581
|View full text |Cite
|
Sign up to set email alerts
|

Social Interaction Behavior in ADHD in Adults in a Virtual Trust Game

Abstract: Alterations in interaction behavior and in the formation of a general attitude toward social partners could be shown in adults with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…However, in both of the VR studies, we manipulated multiple aspects of verbal and non-verbal behaviour to achieve a large effect of trustworthiness and, therefore, detected a large effect on each of the virtual maze measures (Table 7). In Study 3, we manipulated trustworthiness in a more subtle way by making characters play fairly or unfairly in an investment game (Franzen et al, 2011; Lis et al, 2016), and we implemented a low-tech version of the maze task without VR. Perhaps, due to a combination of these design factors, the virtual maze task was not able to detect such strong effects in the third study (Table 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in both of the VR studies, we manipulated multiple aspects of verbal and non-verbal behaviour to achieve a large effect of trustworthiness and, therefore, detected a large effect on each of the virtual maze measures (Table 7). In Study 3, we manipulated trustworthiness in a more subtle way by making characters play fairly or unfairly in an investment game (Franzen et al, 2011; Lis et al, 2016), and we implemented a low-tech version of the maze task without VR. Perhaps, due to a combination of these design factors, the virtual maze task was not able to detect such strong effects in the third study (Table 7).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if a measure shows no correlation between two characters, then that suggests it is sensitive to specific trust rather than generalised trust. In the third study, we implemented a purer manipulation of trustworthiness using the investment game as a manipulation instead of a dependent measure, following two studies by Franzen et al (2011) and Lis et al (2016). In Study 3, we also programmed a low-tech version of the virtual maze task on a standard computer screen to demonstrate how the task could be used in standard laboratories without VR equipment or software.…”
Section: The Virtual Mazementioning
confidence: 99%
“…We propose that the absence of fERN modulations in the ADHD children may be suggestive of an atypical brain reward processing that may reflect different cognitive strategies to solve the task, rather than an impaired SDM ability in these children. Although the literature examining SDM in ADHD is minimal, one behavioral study reported difficulties in ADHD adults in adapting their behavior to the fairness of a partner 56 . Similarly, emerging evidence indicates social cognition difficulties in ADHD 57 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ADHD show greater problems in attention ( 81 83 ), motor control tasks, and working memory tasks ( 84 ). They also have difficulty inhibiting responses and make more risky decisions ( 85 , 86 ), their performance decreases when reinforcement is delayed, and they seem to be more sensitive to reward ( 87 ) and punishment ( 88 ). Likewise, several studies concluded that a relationship exists between ADHD and intrinsic factors such as male gender and greater number of hours a day in the use of video games; along this line, several studies found that playing more than 1 h per day may worsen ADHD symptoms ( 82 , 83 ).…”
Section: Resultsmentioning
confidence: 99%